Pengaruh Cognitive Behaviour Therapy dalam Mencegah Risiko Bunuh Diri pada Siswa SMPN 2 Batu Sangkar - Alice Rosy; Budi Anna Keliat; Dewi Eka Putri (FORIKES, 2020)
Suicide cases in adolescents have increased from year to year. This study aimed to analyze the effect of cognitive behavioral therapy in preventing suicide risk in students at Batu Nangkar 2 Junior High School in 2015. CBT is a combination of cognitive therapy and behavioral therapy designed to change negative thought patterns into positive ones so as to produce changes in behavior. Research design was